2019
DOI: 10.1016/j.concog.2019.102806
|View full text |Cite
|
Sign up to set email alerts
|

Implicit and explicit spatial-numerical representations diverge in number-form synesthetes

Abstract: In number-form (NF) synesthesia-a condition in which people report vivid, automatic and consistent mental layouts for numerical sequences-numbers and space are closely linked. These explicit associations are similar to the implicit associations demonstrated by the Spatial-Numerical Association of Response Codes (SNARC) effect. Thus, NF synesthesia offers a unique opportunity to investigate spatial-numerical associations. We tested implicit and explicit representations in NF synesthetes using a multiple case-st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…When the representation positions of a number conflict with a participant's left/right response effector, the SNARC effect is generated (Basso Moro et al, 2018;Cutini et al, 2014;Dehaene et al, 1993;Fischer & Shaki, 2014). However, some previous studies have shown that the SNARC effect varies in both the direction and processing stage (Dehaene et al, 1993;Fias & van Dijck, 2016;Toomarian et al, 2019;van Dijck & Fias, 2011;Yan et al, 2022). Particularly in the processing stage, a long-standing debate has been whether the SNARC effect occurs only in the early semantic-representation stage (Fischer et al, 2004;Mapelli et al, 2003;Tlauka, 2010), only in the late response-selection stage (Daar & Pratt, 2008;Gevers et al, 2005;Pinto, Pellegrino, Lasaponara, et al, 2021;Yan et al, 2021), or in both stages (Basso Moro et al, 2018;Nan et al, 2021;Zhang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…When the representation positions of a number conflict with a participant's left/right response effector, the SNARC effect is generated (Basso Moro et al, 2018;Cutini et al, 2014;Dehaene et al, 1993;Fischer & Shaki, 2014). However, some previous studies have shown that the SNARC effect varies in both the direction and processing stage (Dehaene et al, 1993;Fias & van Dijck, 2016;Toomarian et al, 2019;van Dijck & Fias, 2011;Yan et al, 2022). Particularly in the processing stage, a long-standing debate has been whether the SNARC effect occurs only in the early semantic-representation stage (Fischer et al, 2004;Mapelli et al, 2003;Tlauka, 2010), only in the late response-selection stage (Daar & Pratt, 2008;Gevers et al, 2005;Pinto, Pellegrino, Lasaponara, et al, 2021;Yan et al, 2021), or in both stages (Basso Moro et al, 2018;Nan et al, 2021;Zhang et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that the SNARC effect varies in both the direction and processing stage ( Dehaene et al, 1993 ; van Dijck and Fias, 2011 ; Fias and van Dijck, 2016 ; Toomarian et al, 2019 ; Yan et al, 2022 ). Particularly in the processing stage, a long-standing debate has been whether the SNARC effect occurs only in the early semantic-representation stage ( Mapelli et al, 2003 ; Fischer et al, 2004 ; Tlauka, 2010 ), only in the late response-selection stage ( Gevers et al, 2005 ; Keus and Schwarz, 2005 ; Daar and Pratt, 2008 ; Colling et al, 2020 ; Yan et al, 2021 ; Pinto et al, 2021a ), or in both stages ( Basso Moro et al, 2018 ; Zhang et al, 2020 ; Nan et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…The visuomotor Simon effect is caused by the exogenous location information of the stimulus, which decreases along RTs since the decay of the visual spatial information. The cognitive Simon effect is caused by the mutual interference between the cognitive coding of the stimulus location and the reaction location, which remains stable or strengthens at longer RTs because the stimulus feature translation into the spatial representation requires more time ( Toomarian et al, 2019 ; Yan et al, 2021 ). Thus, the interference caused by the cognitive Simon effect on the spatial representation of the SNARC effect is more stable.…”
Section: Introductionmentioning
confidence: 99%